EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE, TRANSACTIONAL LEADERSHIP, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PT. WAJO PARTNER MATERIALS IN MAKASSAR - Edo Kurniawan Basri; Serlin Serang; Aryati Arfah (Jurnal Ilmu Manajemen Profitability, 2021)
The effect of transformational leadership style, transactional leadership style, and prganizational culture on employee performance on PT. Bahana Mitra Waji in Makassar. This purpose of this research is to investigate: (1) the effect of transformational leadership style on employee performance, (2) the effect of transactional leadership style on employee performance, and (3) the effect of organizational culture on employee performance. The population of research is all employees of PT. Bahana Mitra Wajo inMakassar totaled to 46 persons with sampling technique using saturated sampling. Analysis method is regression linear multiple by first tested with test of validity and reliability. The results of this research showed that : (1) transformational leadership style significantly effects employee performance, (2) transactional leadership style significantly effects employee performance, and (3) organizational culture significantly effects employee performance. This means that the transformational leadership style is like giving motivations, and transactional leadership style such as giving rewads, and the organizational culture is like having a ne innovation encourage an increase in employee performance measured by achievement of targets, quality and quantity or working together and responsibility for their work